The use of acupuncture for addressing neurological and neuropsychiatric symptoms in patients with long COVID: a systematic review and meta-analysis - Lam, Wai Ching; Wei, Dongjue; Li, Huijuan; Yao, Liang; Zhang, Shiping; Lai, Michael X. Y.; Zheng, Ya; Yeung, Jerry W. F.; Lau, Alexander Y. L.; Lyu, Aiping; Bian, Zhaoxiang; Cheung, Angela M.; et al. (Frontiers in Neurology, 2024)
Importance Acupuncture has been used to treat neurological and neuropsychiatric symptoms in China and other parts of the world. These symptoms, such as fatigue, headache, cognitive impairment, anxiety, depression, and insomnia, are common in people experiencing long COVID. Objective This study aims to explore the feasibility of acupuncture in the treatment of neurological and neuropsychiatric symptoms in long COVID patients. Data Sources A systematic search was conducted in four English and four Chinese databases from inception to 23 June 2023. Literature selection and data extraction were conducted by two pairs of independent reviewers. Study Selection Randomized controlled trials (RCTs) that explored the effect of acupuncture on fatigue, depression, anxiety, cognitive abnormalities, headache, and insomnia were included. Data Extraction and Synthesis RCTs that explored the effect of acupuncture on fatigue, depression, anxiety, cognitive abnormalities, headache, and insomnia were included. A meta-analysis was performed using R software. Heterogeneity was measured using I2. Subgroup analyses were performed focusing on the duration of treatment and acupuncture modalities. The systematic review protocol was registered on PROSPERO (registration number: CRD42022354940). Main outcomes and measures Widely adopted clinical outcome scales included the Fatigue Scale for assessing fatigue, the Hamilton Depression Rating Scale for evaluating depression, the Mini-Mental State Examination for assessing cognitive impairment, the Visual Analog Scale for headache severity, and the Pittsburgh Sleep Quality Index for measuring insomnia. Results A total of 110 RCTs were included in the systematic review and meta–analysis. Overall, acupuncture was found to improve the scores of the Fatigue Scale (vs. medication: mean differences (MD): −2.27, P < 0.01; vs. sham acupuncture: MD: −3.36, P < 0.01), the Hamilton Depression Rating Scale (vs. medication: MD: −1.62, 95%, P < 0.01; vs. sham acupuncture: MD: −9.47, P < 0.01), the Mini–Mental State Examination (vs. medication: MD: 1.15, P < 0.01; vs. sham acupuncture: MD: 1.20, P < 0.01), the Visual Analog Scale (vs. medication: MD: −1.05, P < 0.01; vs. waitlist: MD: −0.48, P=0.04), and the Pittsburgh Sleep Quality Index (vs. medication: MD: −2.33, P < 0.01; vs. sham acupuncture: MD: −4.19, P < 0.01). Conclusion and relevance This systematic review suggested acupuncture as a potentially beneficial approach for the treatment of neurological and neuropsychiatric symptoms, as assessed using clinical scales, and it may have applicability in long COVID patients. Further well-designed clinical studies specifically targeting long COVID patients are needed to validate the role of acupuncture in alleviating long COVID symptoms. Systematic Review Registration PROSPERO, identifier [CRD42022354940].